2015
DOI: 10.1093/jamia/ocv142
|View full text |Cite
|
Sign up to set email alerts
|

Strategizing EHR use to achieve patient-centered care in exam rooms: a qualitative study on primary care providers

Abstract: This study has uncovered the challenges that primary care providers face in integrating the EHR into their work practice, and the strategies they use to overcome these challenges in order to maintain patient-centered care. These findings illuminate the importance of developing "best" practices to improve patient-centered care in today's highly "wired" health environment. These findings also show that more user-centered EHR design is needed to improve system usability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 25 publications
2
42
1
Order By: Relevance
“…27 Interestingly, only 5% of patients seen by faculty reported feeling this way. 27 Recently, papers suggesting strategies for combatting these negative effects have published, 22,10 but they are usually based on physician ideas of how to accomplish patient-centeredness. We have introduced the patient's voice into that discussion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…27 Interestingly, only 5% of patients seen by faculty reported feeling this way. 27 Recently, papers suggesting strategies for combatting these negative effects have published, 22,10 but they are usually based on physician ideas of how to accomplish patient-centeredness. We have introduced the patient's voice into that discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians also believe that screen-sharing can be beneficial. 22 One study videotaped primary care visits, and demonstrated that almost half of the visits included the physician actively sharing the computer screen with patients. 30 In our study, patients reported that screen sharing resulted in increased trust in their doctors, and that not sharing the screen made some suspicious.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations